A novel high-performance supercapacitor based on the innovated ternary CeO2@CoWO4/N-doped graphene nanocomposites - Bahareh Arasteh; Mehdi Shabani-Nooshabadi; Hanieh Ansarinejad (Energy Nexus)
The present work used multiple steps method to fabrication the three component CeO2@CoWO4/N-doped graphene (CCNG) as active material for supercapacitor application for the first time. For this purpose, firstly CoWO4 nanostructure was synthesized via hydrothermal route, after that CeO2 nanoparticles were sonochemicaly grown on CoWO4 nanostructures followed by thermal treatment and overall, CCNG nanocomposites were synthesized through the hydrothermal approach in presence of urea as nitrogen source. As-designed materials were physico-chemically characterized by field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) spectroscopy and Brunauer-Emmett-Teller (BET) tests. The electrochemical capacitive of as-fabricated nanostructures were investigated by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) technologies in 3.0 M KOH solution as electrolyte. Also, molar ratio of Ce2+: Co2+ was optimized and CeO2@CoWO4 with molar ratio 1:2 was selected as the best electrode with specific capacitance of 489.27 F g-1 at constant current density of 3 A g-1. Likewise, the mass ratio of N-doped graphene to active materials was optimized and, CCNG-2 nanocomposites illustrated the highest specific capacitance of 698.18 F g−1 at 3 A g−1, which was greater than that of bare CoWO4 (295.64 F g−1) and CeO2 (293.45 F g-1) at this condition. Furthermore, CCNG-2 nanocomposites exhibited superior cycling stability 91.8 % capacity retention after 1000 cycles at sweeping scan rate of 50 mV s-1, while CeO2@CoWO4 possessed 73.2 % capacity retention at 1000th cycles. These interesting results revealed that the CCNG-2 nanocomposites are capable as a active material for usage in high-performance electrochemical supercapacitors.